Integrated proteomic and metabolomic profiling identifies distinct molecular signatures and metabolic pathways associated with obesity and potential targets for anti-obesity therapies - Li, Yi; Yang, Huawu; Zhang, Xinpeng; He, Xingyu; Liuli, Anke; Li, Rui; Han, Xingyu; Li, Yongmei; Gao, Pan (Frontiers in Endocrinology, 2025)
BackgroundAdipose tissue remodeling induced by bariatric surgery plays a pivotal role in promoting weight loss and metabolic improvement. However, the underlying molecular mechanisms, particularly protein-metabolite regulatory networks, remain poorly understood. This integrative proteomic and metabolomic study identifies key pathway alterations and molecular signatures associated with metabolic phenotypes, offering novel mechanistic insights into the therapeutic efficacy of bariatric surgery.MethodsVisceral adipose tissue samples were analyzed using label-free DIA quantitative proteomics and LC-MS/MS metabolomics. Proteomic and metabolomic data were processed with MaxQuant software and XCMS R package, respectively.ResultsProteomic and metabolomic analyses were performed on visceral adipose tissue from 10 obese patients undergoing sleeve gastrectomy and 10 controls. Proteomic profiling quantified identified 135 differentially expressed proteins (57 upregulated, 78 downregulated), with PHACTR2 and PLIN2 upregulated in obesity and ADAR down-regulated in obesity. Enrichment analyses indicated disruptions in lipid droplet formation, muscle processes, and protein autophosphorylation, with KRT1/MYH9 and NF1/ATR identified as hub proteins. Metabolomics revealed 191 differential metabolites (110 upregulated, 81 downregulated), with 4-Vinylcyclohexene positively correlated with BMI and asparagine-betaxanthin negatively correlated. KEGG analysis showed disturbances in purine/pyrimidine metabolism, AMPK signaling, and cortisol biosynthesis. Integrated protein-metabolite network analysis identified OSBPL10, CUL2, and PRTN3 as potential regulators of lipid metabolism and insulin resistance, offering insights into obesity-associated metabolic dysfunction.ConclusionsThis study integrated proteomic and metabolomic data from visceral adipose tissue obtained through sleeve gastrectomy, identifying obesity-related functional pathways and molecular signatures linked to metabolic phenotypes, highlighting the value of multi-omics in understanding adipose tissue remodeling and postoperative metabolic improvement.